A web-based integrated medical information system for telepathology - Jongsataporn, Thitaphan; Yimmun, Surapun; Suapang, Piyamas; Boontawan, Rodjarin; Dejhan, Kobchai (My University, 2010)
The design and implementation of A Web-based Integrated Medical Information System for Telepathology which server was developed using software such as Borland C++ Builder 5.0, PHP and MySQL for image archive, image compression, image processing and image transmission. The system provides the following facilities: (1) DICOM-format image archive. (2) Medical Image Compression based on JPEG and JPEG2000. and (3) DICOM viewer. The results shown that (1) our system can also convert the image data both single frame and multiframe in normal or automatic DICOM process into the standard DICOM 3.0 format without altering the image data. (2) The resulting images are then compressed with two different techniques - JPEG and JPEG2000. The significant advantage of JPEG2000 over normal JPEG is that the error from JPEG2000 compression is smaller than the error from JPEG. Nevertheless, both methods share a similar mishap; when the compression ratio increases, they both generate more error than the processes on lower compression ratio. And (3) our system can open single frame and continuous frames, each of which can exhibit information in .dcm file format with no distortion and digital image processing based on local contrast enhancement, adaptive interpolators techniques and cine loop. The system has been developed and provided medical image services over long distance which showed the usefulness of our approach.
Keywords: Dicom standard; Image archive; Image compression; Image processing; Telepathology